2020
DOI: 10.1609/aaai.v34i04.6047
|View full text |Cite
|
Sign up to set email alerts
|

Stealthy and Efficient Adversarial Attacks against Deep Reinforcement Learning

Abstract: Adversarial attacks against conventional Deep Learning (DL) systems and algorithms have been widely studied, and various defenses were proposed. However, the possibility and feasibility of such attacks against Deep Reinforcement Learning (DRL) are less explored. As DRL has achieved great success in various complex tasks, designing effective adversarial attacks is an indispensable prerequisite towards building robust DRL algorithms. In this paper, we introduce two novel adversarial attack techniques to stealthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…In addition, the effectiveness of an universal adversarial attack against DRL interpretations (i.e., UADRLI) has been verified by the theoretical analysis [204], from which the attacker can add the crafted universal perturbation uniformly to the environment states in a maximum number of steps to incur minimal damage. In order to stealthily attack the DRL agents, the work in [205] has injected adversarial samples in a minimal set of critical moments while causing the most severe damage to the agent. Another work in [206] has formulated an optimization framework in a stealthy manner for finding an optimal attack for different measures of attack cost, and solve it with an offline or online setting.…”
Section: • Model Inversion By Casting the Model Inversion Taskmentioning
confidence: 99%
“…In addition, the effectiveness of an universal adversarial attack against DRL interpretations (i.e., UADRLI) has been verified by the theoretical analysis [204], from which the attacker can add the crafted universal perturbation uniformly to the environment states in a maximum number of steps to incur minimal damage. In order to stealthily attack the DRL agents, the work in [205] has injected adversarial samples in a minimal set of critical moments while causing the most severe damage to the agent. Another work in [206] has formulated an optimization framework in a stealthy manner for finding an optimal attack for different measures of attack cost, and solve it with an offline or online setting.…”
Section: • Model Inversion By Casting the Model Inversion Taskmentioning
confidence: 99%
“…Different from adversarial attacks which usually act during the inference process of a neural model [17,38,49,53,63,63,66,74,84,85], backdoor attacks hack the model during training [10,22,40,51,61,62,75,82]. Defending against such attacks is challenging [8,23,37,41,57,73] because users have no idea of what kinds of poison has been injected into model training.…”
Section: Backdoor Attack and Defensementioning
confidence: 99%
“…Similarly, Lin et al [16] proposed to attack during a chosen subset of time steps. Applications of this type of attacks to autonomous driving have been shown to be effective [17], [18]. Weng et al [19] showed that learning the dynamics of agents and environments improves the efficacy of the attack in comparison to model-free methods.…”
Section: Introductionmentioning
confidence: 99%